Perivascular space alteration in idiopathic and familial Parkinson's disease: Neuroimaging / differential diagnosis. (7th December 2020) - Murdos, Amjad; Sheikh‐Bahaei, Nasim; Toga, Arthur W.; Sepehrband, Farshid; ,
Abstract: Background: Parkinson's Disease is the second most prevalent neurodegenerative diseases today. There is a growing body of evidence suggesting overlap between Alzheimer's disease and many Parkinson related neurodegenerative processes. Understanding the vascular impact in patients with Parkinson's disease can provide new insight on pathological progression and treatment options. Dilation of perivascular spaces has been an important measure of vascular insult in the context of glia‐lymphatic clearance and neurodegenerative diseases. The role of microvascular changes and particularly dilated perivascular spaces in Parkinson's disease, has not been investigated. Differences in perivascular spaces among patient with idiopathic and familial Parkinson's disease can provide novel insight on the implications of the genetic components pertaining to Parkinson's disease. Method: Total of 470 individuals were analyzed from the PPMI database. Subjects were grouped based on their genetic status of their disease: idiopathic Parkinson's Disease (n=201), familial Parkinson's Disease (n=71), healthy controls without genetic risk factor (n=94) and healthy controls with genetic risk factor (n=104). To study the impact of brain glia‐lymphatic pathway pathology on the clinical status of idiopathic and familial Parkinson's disease, total perivascular space volume was compared between these patient populations using a newly developed technique (Figure 1). Result: The perivascular spaces were significantly larger in the idiopathic and familial Parkinson's disease subjects compared with the idiopathic and familial control subjects. Interestingly, across different groups the lowest perivascular space volume fraction was observed in the healthy control with genetic risk factor, suggesting a potential protective or compensatory mechanism relating to vascular or glia‐lymphatic system (Figure 2). Conclusion: Our findings showed that individuals with symptomatic Parkinson's disease have more enlarged perivascular spaces compared to clinically intact controls independent of their genetic predisposition. It suggests that microvascular changes and particularly perivascular spaces might contribute to the neurodegenerative symptoms through parallel pathways additional to the primary pathological process. These results are very similar to the effect of perivascular spaces in Alzheimer's disease. More interestingly, our data showed that presence of Parkinson's genetic factors, does not increase the risk of glia‐lymphatic impairment while in the later stages this impairment can contribute into the clinical picture.